2011
DOI: 10.1016/j.jval.2011.08.1334
|View full text |Cite
|
Sign up to set email alerts
|

PDB31 Cost of Diabetes in Croatia Impact of Complications on the Costs of Type II Diabetes

Abstract: Association (ADA) guidelines were simulated. Cost of treatment and complications were based on officially published sources for medicines prices (www.mh.government.bg), for hospital charges (www.nhif.bg) and verified by expert opinion survey (1 BGN ϭ 0.51 EUR). Future costs were discounted with 5%. RESULTS: Treatment to targets postpones minor complications by up to 4 years, delays major complications by 3 to 4 years and extends life expectancy from diagnosis by 3 years compared with the baseline scenario. Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Study characteristics are presented in Table 1. Four studies [10,[32][33][34] reported burden-of-illness values (i.e., population-level results), whereas 20 studies [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] reported cost-of-illness values (i.e., patient-level results). Studies from 13 countries (Brazil, Croatia, Estonia, India, Italy, Japan, Mexico, Scotland, South Korea, Spain, Sweden, the United Kingdom, and the United States) were represented in this review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study characteristics are presented in Table 1. Four studies [10,[32][33][34] reported burden-of-illness values (i.e., population-level results), whereas 20 studies [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] reported cost-of-illness values (i.e., patient-level results). Studies from 13 countries (Brazil, Croatia, Estonia, India, Italy, Japan, Mexico, Scotland, South Korea, Spain, Sweden, the United Kingdom, and the United States) were represented in this review.…”
Section: Resultsmentioning
confidence: 99%
“…Three other studies reported on patient populations from Asia (India [44], Japan [39], and South Korea [43]). A further seven studies [33,35,40,46,47,50,52] reported results based on a European population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it represents a growing burden to health economy. The total treatment cost of T2DM and its complications in Croatia amounted to 11.49% of the Croatian Health Insurance Fund’s budget in 2009, ie, to 351.7 million EUR: 50.2 million EUR for direct medical costs of diabetes treatment and monitoring, 301.5 million EUR for treatment of diabetes-related chronic complications, and 4.6 million EUR for additional indirect costs ( 2 ). It is well established that the risk of microvascular and macrovascular complications is related to glycemia.…”
mentioning
confidence: 99%
“…The total cost of type 2 DM in Croatia amounted to e351.7 million in 2009, i.e. 11.49% of the national insurer's budget 3 . This cost included e50.2 million for care and medications used directly in DM treatment (14.28%) and e301.5 million stemming from diabetes-related chronic complications (85.72%).…”
Section: Introductionmentioning
confidence: 99%